Mucosal Metastasis of Prostate Adenocarcinoma Presenting as a Colon Polyp Found at 15 Years After Radical Prostatectomy: A Case Report and Review of the Literature. (21st September 2018) - Lobo, Monica; Collins, Victoria; Crawford, Byron; Nakanishi, Yukihiro
Abstract: Prostate adenocarcinoma is known to metastasize to various parts of the body such as the vertebrae, regional lymph nodes, lungs, liver, and brain. Metastasis to the colon from prostate adenocarcinoma is generally due to the direct extension of prostate adenocarcinoma. Metastatic prostate adenocarcinoma presenting as a colon polyp is extremely rare. We report an extremely rare case of mucosal metastasis of prostate adenocarcinoma presenting as a colon polyp in a 74-year-old man with a history of radical prostatectomy for prostate adenocarcinoma 15 years ago. The patient was referred to our facility for evaluation of colonic lesions. A total colonoscopy showed four colon polyps: one tubular adenoma in the hepatic flexure, one tubular adenoma in the transverse colon, and two flat polyps in the rectosigmoid colon. The two flat polyps of the rectosigmoid colon measuring less than 5 mm were removed by cold snare polypectomy. Microscopically, one of the polyps showed a hyperplastic change, and the other one showed a mucosal adenocarcinoma with intact muscularis mucosae, which stained positive for prostate-specific antigen and prostate-specific acid phosphatase. Although the previous prostatectomy slides are unavailable for comparison, the morphology and immunoprofile are consistent with metastatic prostate adenocarcinoma. The findings of a polypoid lesion during total colonoscopy and intact muscularis mucosae along with the immunoprofile of the tumor cells support the diagnosis of mucosal metastasis of prostate adenocarcinoma presenting as a colon polyp. Subsequent abdominal computed tomography scan showed a mass measuring 5.1 × 4.4 × 4.0 cm interposed between the sigmoid colon and the dome of the urinary bladder suggestive of recurrent prostate adenocarcinoma in view of the presence of colonic mucosal metastasis of prostate adenocarcinoma.